Urethane foam compact and heat dissipation structure using the same

JP2025025262APending Publication Date: 2025-02-21SUMITOMO RIKO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023129881
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-21

Smart Images

  • Figure 2025025262000001_ABST
    Figure 2025025262000001_ABST
Patent Text Reader

Abstract

To provide an urethane foam compact which has softness and an excellent heat conductivity and can be used as a heat conductive material, and provide a heat dissipation structure using the same.SOLUTION: An urethane foam compact has: a base material formed by a polyurethane foam; and a composite particle that is contained in the base material, and has a heat conductive particle and a magnetic particle adhered to a front surface of the heat conductive particle by a binder. In the urethane foam compact, the composite particle is directed to a heat conductive direction. The urethane foam compact has a compression part compressed to a heat conductive direction at 5% or more and 65% or less of a compression rate. The heat dissipation structure that discharges heat of a heat generation body comprises a heat radiation body and the urethane foam compact, and the compression part of the urethane foam compact is arranged to between the heat generation body and the heat radiation body.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a urethane foam molded product used as a thermally conductive material, and a heat dissipation structure using the same. [Background technology]

[0002] In battery packs and electronic devices mounted on electric vehicles, heat sinks, cooling plates, and other heat dissipators are used to dissipate heat generated during use to the outside. A thermally conductive material called a thermal interface material (TIM) is placed between the heat generating body and the heat dissipating body to reduce the thermal resistance between the heat generating body and the heat dissipating body and improve the heat dissipation. For example, as described in Patent Documents 1 and 2, various materials such as grease, gel, phase change material (PCM), and sheet-shaped molded body have been developed as thermally conductive materials depending on the application. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-88108 A [Patent Document 2] JP 2022-121447 A [Patent Document 3] International Publication No. 2013 / 042611 Summary of the Invention [Problem to be solved by the invention]

[0004] When using thermally conductive grease among thermally conductive materials, in addition to dripping, pump-out, in which the grease is pushed out from between the members due to deformation of the applied member, becomes a problem. When voids are generated between the grease and the member due to pump-out, the adhesion between the two is reduced and the thermal resistance increases. As a material that avoids dripping and pump-out, a solid material such as a thermally conductive sheet is mentioned. The above-mentioned Patent Document 2 describes a thermally conductive sheet in which a thermally conductive filler is dispersed in a binder component that is a mixture of a silicone matrix and a hydrocarbon-based compound. The battery cells contained in the battery pack repeatedly expand and contract with charging and discharging. Electronic components in electronic devices may also undergo deformation such as warping due to repeated heating and cooling. Therefore, a solid thermally conductive material is required to have flexibility that can follow the deformation of the heating element and the like. However, a material in which a thermally conductive filler is mixed into a solid polymer matrix (substrate), such as the thermally conductive sheet described in Patent Document 2, is poor in flexibility. In order to increase the thermal conductivity, the content of the thermally conductive filler is preferably large, but increasing the content reduces flexibility and increases the mass.

[0005] As a flexible material, foams such as polyurethane foam are known. However, foams have many bubbles inside and have low thermal conductivity. In this regard, Patent Document 3 describes a polyurethane foam molded body in which composite particles, which are a composite of thermally conductive particles and magnetic particles, are oriented and arranged in polyurethane foam, and a heat conduction path is formed in the orientation direction, thereby improving heat dissipation. However, since the polyurethane foam molded body was developed as a sound absorbing material, its thermal conductivity is not sufficient as a thermal conductive material whose main purpose is heat dissipation, and it is difficult to apply it as it is. In this case, if the content of the composite particles is increased, the thermal conductivity may be increased, but if the content is increased, the flexibility decreases and the mass increases. In addition, there is a risk that the foaming and curing reaction of the polyurethane foam may be affected and the moldability may be hindered.

[0006] The present disclosure has been made in consideration of the above-mentioned circumstances, and has an objective of providing a urethane foam molding that is flexible, has excellent thermal conductivity, and can be used as a thermal conductive material, and a heat dissipation structure using the same. [Means for solving the problem]

[0007] (1) In order to solve the above problems, the urethane foam molded product of the present disclosure comprises a base material made of polyurethane foam, and composite particles contained in the base material, the composite particles having thermally conductive particles and magnetic particles bonded to the surfaces of the thermally conductive particles with a binder, the composite particles being oriented in the direction of thermal conduction, and characterized in having a compressed portion compressed in the direction of thermal conduction at a compression ratio of 5% or more and 65% or less.

[0008] The urethane foam molded body of the present disclosure has a compressed portion compressed at a specific compression ratio of 5% to 65% in the heat conduction direction. When the urethane foam molded body is compressed, the bubbles are crushed. This can increase the thermal conductivity. The compression direction of the urethane foam molded body is the heat conduction direction, which is also the orientation direction of the composite particles. That is, the composite particles are oriented and connected in a line, forming a heat conduction path in the base material. Therefore, when the urethane foam molded body is compressed in the heat conduction direction, the composite particles approach each other while maintaining the orientation state of the composite particles, and the composite particles are likely to contact each other. This can increase the thermal conductivity. In this way, according to the urethane foam molded body of the present disclosure, a large thermal conductivity can be achieved in the compressed portion by the action of the bubbles and composite particles, even without increasing the content of the composite particles. Since the content of the composite particles does not increase, it is possible to avoid a decrease in flexibility and an increase in mass. In addition, there is no effect on the foaming and curing reaction or moldability of the polyurethane foam.

[0009] The base material of the urethane foam molded body of the present disclosure is a foam having air bubbles. Therefore, compared with conventional molded bodies in which the base material is a solid polymer material, it is flexible and lightweight. In addition, since it has cushioning properties due to the air bubbles, it is difficult to pump out even if the member to which it is applied is deformed. In this way, the urethane foam molded body of the present disclosure is flexible and relatively lightweight, and can be used as a heat conductive material by utilizing the high thermal conductivity in the compressed part.

[0010] (2) In the above configuration, the content of the composite particles may be 5% by volume or more and 50% by volume or less, assuming the volume of the urethane foam molded body to be 100% by volume. This configuration can reduce the weight of the urethane foam molded body. In addition, the composite particles can improve the thermal conductivity while minimizing the effect on the foaming and curing reaction and moldability.

[0011] (3) In any of the above configurations, the porosity of the portion other than the compressed portion may be 4% by volume or more and 40% by volume or less, assuming that the volume of the urethane foam molded body is 100% by volume. The porosity is the volume ratio of the holes (air bubbles) contained in the urethane foam molded body. If the porosity is too small, that is, if the amount of air bubbles in the polyurethane foam is too small, compression cannot be performed sufficiently. Conversely, if the porosity is too large, the thermal conductivity of the urethane foam molded body will be low. With this configuration, it is possible to achieve a compressed portion with a high compression ratio of 65% while ensuring the desired thermal conductivity.

[0012] (4) In any of the above configurations, the thermally conductive particles may be flaky or fibrous, and the degree of orientation of the composite particles in the compressed section may be 0.2 or more. The closer the degree of orientation of the composite particles is to 1, the smaller the inclination of the long axis of the composite particles with respect to the thermal conduction direction of the urethane foam molding, and the closer the long axis direction is to the thermal conduction direction (becomes parallel to the thermal conduction direction). With this configuration, the composite particles can be brought close to each other without disrupting their orientation. This can increase the thermal conductivity of the compressed section.

[0013] (5) In any of the above configurations, the thermally conductive particles may include expanded graphite particles. The expanded graphite particles are formed by inserting a substance that generates gas when heated between layers of scaly graphite. When heat is applied to the expanded graphite particles, the generated gas expands the gap between the layers and forms a layer that is stable against heat and chemicals. The formed layer acts as a heat insulating layer and prevents the transfer of heat, thereby providing a flame retardant effect.

[0014] Usually, a urethane foam molded body that has been given flame retardancy has a dropping action that drops the fire and suppresses the spread of the fire even when exposed to a flame. However, if magnetic particles are blended, the dropping action is impaired, and the self-extinguishing property of the urethane foam molded body may be reduced. In the urethane foam molded body of the present disclosure, the composite particles are oriented in the direction of heat conduction. Therefore, the heat applied to the urethane foam molded body is easily transferred to the thermally conductive particles, and the expanded graphite particles quickly reach the expansion start temperature. This allows the flame retardant effect of the expanded graphite particles to be quickly exerted. Therefore, according to this configuration, the decrease in the self-extinguishing property of the urethane foam molded body can be suppressed, and the flame retardancy can be maintained.

[0015] (6) In any of the above configurations, the base material may further include insulating inorganic particles dispersed therein. When insulating inorganic particles are present in the base material, the composite particles are less likely to be electrically conductive with each other, and the urethane foam molded body is provided with electrical insulation. When the insulating inorganic particles have a relatively high thermal conductivity, in addition to the heat conduction path through the composite particles, a heat conduction path through the insulating inorganic particles is also formed. This further improves the thermal conductivity of the urethane foam molded body. When the insulating inorganic particles have flame retardancy, the flame retardancy of the urethane foam molded body is improved.

[0016] (7) In any of the above configurations, the compression section may be arranged between the heat generating body and the heat dissipating body. With this configuration, the high thermal conductivity of the compression section can be utilized to reduce the thermal resistance between the heat generating body and the heat dissipating body. The urethane foam molded body of this configuration is useful as a thermally conductive material that is relatively lightweight and flexible enough to follow the deformation of the heat generating body, etc.

[0017] (8) In any of the above configurations, the entire urethane foam molded body may be configured to consist of the compressed portion. The urethane foam molded body of this configuration may be molded into a sheet shape and used as a thermally conductive sheet, for example.

[0018] (9) The heat dissipation structure of the present disclosure is a heat dissipation structure that dissipates heat from a heat generating body, and is characterized in that it includes a heat dissipation body and a urethane foam molded body having any of the above configurations, and the compressed portion of the urethane foam molded body is disposed between the heat generating body and the heat dissipation body. As described above, the urethane foam molded body of the present disclosure is flexible and relatively lightweight, and has high thermal conductivity in the compressed portion. Therefore, the heat dissipation structure of the present disclosure can be made lighter, and the compressed portion disposed between the heat generating body and the heat dissipation body has excellent followability to deformation of the heat generating body and the like. In addition, pump-out, in which the compressed portion is pushed out from between the heat generating body and the heat dissipation body, is unlikely to occur. According to the heat dissipation structure of the present disclosure, since the heat dissipation from the heat generating body to the heat dissipation body is improved, for example, when a cooling plate using a refrigerant is used as the heat dissipation body, the output required for cooling can be reduced, and the cooling device can be made smaller. Effect of the Invention

[0019] The urethane foam molded body of the present disclosure is flexible and relatively lightweight, and can be used as a heat-conducting material by utilizing the high thermal conductivity of the compressed portion. The heat dissipation structure of the present disclosure can improve the heat dissipation from the heat generating body to the heat sink. In addition, the weight can be reduced, and the compressed portion disposed between the heat generating body and the heat sink has excellent conformity to deformation of the heat generating body and is less likely to pump out. [Brief description of the drawings]

[0020] [Figure 1] 1 is a schematic cross-sectional view of a battery pack in which a heat dissipation structure according to the present disclosure is disposed. [Diagram 2] 1 is a graph showing thermal conductivity versus compressibility of a urethane foam molded body. [Diagram 3] 1 is a graph showing the degree of orientation of composite particles versus the compressibility of a urethane foam molding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, embodiments of the urethane foam molded body and the heat dissipation structure of the present disclosure will be described. Note that the embodiments are not limited to the following embodiments, and various modifications and improvements that can be made by those skilled in the art can be made.

[0022] <Urethane foam molding> The urethane foam molded product of the present disclosure has a substrate made of polyurethane foam and composite particles contained in the substrate, the composite particles being oriented in the direction of thermal conduction and having a compressed portion compressed in the direction of thermal conduction at a compression ratio of 5% or more and 65% or less.

[0023] [Base material] The shape, size, etc. of the substrate are not particularly limited and may be appropriately determined depending on the application. The polyurethane foam of the substrate is produced from a urethane foam resin raw material such as a polyisocyanate component and a polyol component. The urethane foam resin raw material may be prepared from a known raw material such as a polyol or a polyisocyanate. The polyol may be appropriately selected from polyhydric hydroxy compounds, polyether polyols, polyester polyols, polymer polyols, polyether polyamines, polyester polyamines, alkylene polyols, urea-dispersed polyols, melamine-modified polyols, polycarbonate polyols, acrylic polyols, polybutadiene polyols, phenol-modified polyols, etc. The polyisocyanate may be appropriately selected from, for example, tolylene diisocyanate, phenylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, triphenylmethane triisocyanate, polymethylene polyphenylisocyanate, naphthalene diisocyanate, and derivatives thereof (for example, prepolymers obtained by reaction with polyols, modified polyisocyanates), and the like.

[0024] The polyurethane foam resin raw material may further contain a catalyst, a blowing agent, a foam stabilizer, a plasticizer, a crosslinking agent, a chain extender, a flame retardant, an antistatic agent, a viscosity reducer, a stabilizer, a filler, a colorant, and the like. For example, the catalyst may be an amine catalyst such as tetraethylenediamine, triethylenediamine, or dimethylethanolamine, or an organometallic catalyst such as tin laurate or tin octanoate. The blowing agent is preferably water. Other than water, examples of the foam stabilizer include methylene chloride, fluorocarbons, and CO2 gas. The foam stabilizer may be a silicone foam stabilizer, and the crosslinking agent may be triethanolamine or diethanolamine.

[0025] [Composite particles] The composite particles contained in the base material are particles in which magnetic particles or the like are bonded to the surface of the core thermally conductive particle by a binder. The thermally conductive particles are non-magnetic particles with a relatively large thermal conductivity. In this specification, diamagnetic and paramagnetic materials other than ferromagnetic and antiferromagnetic materials are referred to as non-magnetic materials. For example, the thermal conductivity of the thermally conductive particles is preferably 200 W / m·K or more. Examples of the material of the thermally conductive particles include carbon materials such as graphite and carbon fiber. In addition, aluminum, gold, silver, copper, and alloys using these as the base material may be used. The thermally conductive particles may be single particles or aggregate particles in which multiple particles are integrated.

[0026] The shape of the thermally conductive particles is not particularly limited as long as it can be composited with other particles such as magnetic particles. For example, various shapes such as flaky, fibrous, columnar, spherical, elliptical, and oval spheres (a pair of opposing hemispheres connected by a cylinder) can be adopted. When the thermally conductive particles have a shape other than a sphere, the contact area between the composite particles is large. This makes it easier to ensure a heat conduction path and increases the amount of heat conducted. For example, flaky and fibrous shapes are suitable. In this case, the aspect ratio of the thermally conductive particles is preferably 1.2 or more. Here, the aspect ratio is the ratio of the long axis length to the short axis length of the particle, and for example, in the case of flaky particles, it means the length of the longest part / the length of the shortest part, and in the case of fibrous particles, it means the fiber length / fiber diameter.

[0027] Graphite particles, even those with a large aspect ratio, can be obtained at a low cost compared to metal particles. For this reason, graphite particles are suitable as thermally conductive particles. Examples of graphite include natural graphite such as scaly graphite, scaly graphite, and earthy graphite, and artificial graphite. Artificial graphite is less likely to become scaly. For this reason, natural graphite is suitable because it is scaly and has a high effect of improving thermal conductivity. In addition, as graphite, expanded graphite in which a substance that generates gas when heated is inserted between the layers of scaly graphite may be used. When heat is applied to the expanded graphite, the generated gas expands the gap between the layers and forms a layer that is stable against heat and chemicals. This stable layer becomes a heat insulating layer and prevents the transfer of heat, thereby providing a flame retardant effect. Therefore, in consideration of flame retardancy, expanded graphite particles are suitable as thermally conductive particles. The expanded graphite particles may be appropriately selected in consideration of the expansion start temperature, expansion coefficient, and the like. The expansion initiation temperature must be higher than the heat generation temperature during molding of the urethane foam molded article, so expanded graphite particles with an expansion initiation temperature of 150° C. or higher are preferred.

[0028] From the viewpoint of increasing the thermal conductivity, the median diameter of the thermally conductive particles is desirably 100 μm or more, and more preferably 700 μm or more. On the other hand, if the thermally conductive particles are too large, there is a risk that the molded body will become brittle due to cracks originating from the thermally conductive particles. Therefore, the median diameter of the thermally conductive particles is desirably 3000 μm or less, and more preferably 2000 μm or less. Unless otherwise specified, the median diameter in this specification refers to the value (D 50 For commercially available products, the catalog values ​​may be used.

[0029] The magnetic particles may be any particles capable of orienting the composite particles, and are preferably, for example, ferromagnetic materials such as iron, nickel, cobalt, gadolinium, stainless steel, magnetite, maghemite, manganese zinc ferrite, barium ferrite, strontium ferrite, etc., antiferromagnetic materials such as MnO, Cr2O3, FeCl2, MnAs, etc., and alloy particles using these. Among them, iron, nickel, cobalt, and their iron-based alloys (including stainless steel) are preferable from the viewpoint of being easily available as fine particles and having high saturation magnetization. In particular, iron is relatively inexpensive and easily available, so that it can reduce manufacturing costs and is suitable for mass production.

[0030] The magnetic particles may be directly attached to the surface of the thermally conductive particles, or may be indirectly attached via insulating inorganic particles, which will be described later. The magnetic particles may be attached only to a part of the surface of the thermally conductive particles, or may be attached so as to cover the entire surface. The size of the magnetic particles may be appropriately determined in consideration of the size of the thermally conductive particles, the orientation of the composite particles, and the thermal conductivity between the composite particles. For example, the particle diameter of the magnetic particles is preferably 1 / 10 or less of the particle diameter of the thermally conductive particles. In this case, the "particle diameter" is the equivalent diameter of a sphere of equal volume. When the size of the magnetic particles is reduced, the saturation magnetization of the magnetic particles tends to decrease. Therefore, in order to orient the composite particles with a smaller amount of magnetic particles, it is desirable to set the median diameter of the magnetic particles to 100 nm or more. It is more preferable to set it to 1 μm or more, and even more preferable to set it to 5 μm or more.

[0031] The shape of the magnetic particles is not particularly limited. For example, when the shape of the magnetic particles is flat, the distance between adjacent thermally conductive particles is shorter than when the magnetic particles are spherical. This improves the thermal conductivity between adjacent composite particles. As a result, the thermal conductivity of the urethane foam molding is improved. In addition, when the shape of the magnetic particles is flat, the magnetic particles and the thermally conductive particles are in contact with each other on the surface. In other words, the contact area between the two particles is large. This improves the adhesive force between the magnetic particles and the thermally conductive particles. Therefore, the magnetic particles are less likely to peel off. In addition, the thermal conductivity between the magnetic particles and the thermally conductive particles is also improved. For these reasons, it is desirable to use flaky particles as the magnetic particles.

[0032] From the viewpoint of enabling the composite particles to be oriented even in a relatively weak magnetic field, the content of the magnetic particles is desirably 20% by mass or more, where the mass of the thermally conductive particles in the substrate is taken as 100% by mass. From the viewpoint of cost reduction and weight reduction, the content of the magnetic particles is desirably 130% by mass or less. It is more preferable that the content is 100% by mass or less, and more preferably 80% by mass or less.

[0033] The binder that bonds the thermally conductive particles and the magnetic particles may be appropriately selected in consideration of the adhesiveness and the effect on the foaming and curing reaction. A water-soluble polymer is preferable because it has little effect on the foaming and curing reaction and is environmentally friendly. Examples include methyl cellulose, carboxymethyl cellulose, hydroxypropyl methyl cellulose, polyvinyl alcohol, and starch. Among them, starch is preferable because it is relatively inexpensive, has high adhesion, and has excellent granulation properties.

[0034] The thermally conductive particles and the magnetic particles are conductive. Therefore, the composite particles are aligned and oriented to form a conductive path in the substrate. For example, a composite particle can be formed by adhering insulating inorganic particles to the surface of the thermally conductive particle in addition to the magnetic particles with a binder. In this way, even if the composite particles are oriented, the electrical resistance between adjacent composite particles can be increased or the electrical connection can be cut off. As a result, electrical insulation can be imparted to the urethane foam molded body.

[0035] The insulating inorganic particles may be particles of an inorganic material having insulating properties. Examples of insulating inorganic materials include aluminum hydroxide, aluminum oxide, aluminum nitride, magnesium hydroxide, magnesium oxide, talc, calcium carbonate, clay, mica, and silica. These may be used alone or in combination of two or more. Among them, talc and mica are preferable because they are flaky and have excellent covering properties. In addition, from the viewpoint of not inhibiting the thermal conductivity between composite particles, those with a relatively high thermal conductivity may be used.

[0036] The insulating inorganic particles may be directly bonded to the surface of the thermally conductive particles, or may be indirectly bonded via magnetic particles or the like. The insulating inorganic particles may be bonded to only a part of the surface of the thermally conductive particles, or may be bonded to cover the entire surface. From the viewpoint of increasing the electrical resistance between the composite particles and improving the electrical insulation of the urethane foam molding, it is desirable that the insulating inorganic particles are disposed in the outermost layer of the composite particles. The binder that bonds the magnetic particles to the thermally conductive particles and the binder that bonds the insulating inorganic particles may be the same or different.

[0037] The size of the insulating inorganic particles may be appropriately determined in consideration of the adhesiveness to the thermally conductive particles and the magnetic particles, and the electrical insulation and thermal conductivity between the composite particles. If the insulating inorganic particles are too large, the adhesiveness and the thermal conductivity between the composite particles will decrease. For example, it is desirable that the particle diameter of the insulating inorganic particles is 1 / 10 or less of the particle diameter of the thermally conductive particles. In this case, the "particle diameter" is the equivalent diameter of a sphere of equal volume. For example, the median diameter of the insulating inorganic particles may be 1 μm or more and 20 μm or less.

[0038] The shape of the insulating inorganic particles is not particularly limited. For example, when the insulating inorganic particles are flat, the distance between adjacent thermally conductive particles can be made shorter than when the insulating inorganic particles are spherical. Therefore, the thermal conductivity between adjacent composite particles is less likely to be hindered. In addition, the contact area with the thermally conductive particles is increased, making the insulating inorganic particles less likely to peel off.

[0039] The content of the composite particles may be determined in consideration of the mass, flexibility, thermal conductivity, effect on the foaming and curing reaction of the polyurethane foam, moldability, etc. of the urethane foam molded body. In order to achieve the desired thermal conductivity, the content of the composite particles is desirably 5% by volume or more, assuming that the volume of the urethane foam molded body is 100% by volume. It is more preferable to set it to 10% by volume or more. On the other hand, from the viewpoints of reducing the weight of the urethane foam molded body, maintaining its flexibility, not inhibiting the foaming and curing reaction, and improving moldability, it is desirably the content of the composite particles is 50% by volume or less, and it is more preferable to set it to 20% by volume or less.

[0040] The composite particles contained in the base material are oriented in the heat conduction direction of the urethane foam molding. The closer the orientation direction of the composite particles is to the heat conduction direction, the more the thermal conductivity is improved. For example, when the thermally conductive particles are flaky or fibrous, the degree of orientation of the composite particles in the compressed section is desirably 0.2 or more. The degree of orientation of the composite particles is an index showing the degree of inclination of the long axis of the composite particles with respect to the heat conduction direction of the urethane foam molding. The closer the degree of orientation is to 1, the smaller the inclination of the long axis of the composite particles is, and the closer the long axis direction is to the heat conduction direction (parallel to the heat conduction direction). By setting the degree of orientation of the composite particles to 0.2 or more, the composite particles can be brought close to each other without losing their orientation state. This allows the thermal conductivity of the compressed section to be increased.

[0041] The degree of orientation of the composite particles in this specification is a value obtained by the following method. First, a high-resolution 3D X-ray microscope "nano3DX" manufactured by Rigaku Corporation is used to perform X-ray CT (Computerized Tomography) measurement of a sample of the compressed part of the urethane foam molding. Next, the obtained tomographic image data is subjected to fiber orientation analysis using 3D CT software ("VGStudio (registered trademark) MAX" manufactured by Volume Graphics, Inc. Then, one composite particle is regarded as a collection of voxels, which are the smallest unit of X-ray CT measurement, the connection direction of the voxels is expressed as a tensor, and the heat conduction direction component of the tensor is calculated as the degree of orientation.

[0042] [Other ingredients] The urethane foam molded body of the present disclosure may contain components other than the composite particles in the base material to the extent that the effects of the present disclosure are not impaired. For example, when insulating inorganic particles are dispersed in the base material, the composite particles are less likely to be conductive with each other, and the electrical insulation of the urethane foam molded body is improved. The type of insulating inorganic particles dispersed in the base material may be the same as or different from the insulating inorganic particles added as constituent particles of the composite particles. The shape of the insulating inorganic particles is not particularly limited, and may be spherical or flaky. The insulating inorganic particles may be one type or two or more types. As the insulating inorganic particles, the above-mentioned aluminum hydroxide, aluminum oxide, aluminum nitride, magnesium hydroxide, magnesium oxide, talc, calcium carbonate, clay, mica, silica, etc. are suitable. When the thermal conductivity of the insulating inorganic particles is relatively high, in addition to the heat conduction path by the composite particles, a heat conduction path by the insulating inorganic particles is also formed. Therefore, from the viewpoint of increasing the thermal conductivity of the urethane foam molded body, those with a relatively high thermal conductivity, for example, those with a thermal conductivity of 5 W / m·K or more, are suitable. Furthermore, when the insulating inorganic particles have flame retardancy, the flame retardancy of the urethane foam molding is improved. For example, aluminum hydroxide is preferable because it has a relatively high thermal conductivity and flame retardancy.

[0043] The size of the insulating inorganic particles dispersed in the base material is not particularly limited, but it is desirable to have large particles with a median diameter of 55 μm or more and 200 μm or less. If the median diameter is 55 μm or more, the contact area with the polyurethane foam of the base material is small. This suppresses deterioration due to hydrolysis of polyurethane when the insulating inorganic particles are particles that react with water and show alkalinity. On the other hand, if the median diameter is 200 μm or less, there is little effect on moldability.

[0044] Considering the effect on the foaming and curing reaction of the polyurethane foam and moldability, the content of the insulating inorganic particles dispersed in the base material is desirably 20% by volume or less, and more desirably 15% by volume or less, when the volume of the urethane foam molded product is taken as 100% by volume. In addition, in order to obtain the desired effects such as imparting electrical insulation and improving thermal conductivity, the content is desirably 5% by volume or more, and more desirably 8% by volume or more.

[0045] [Compression section] The urethane foam molded article of the present disclosure has a compressed portion compressed at a compression ratio of 5% to 65% in the heat conduction direction. The compression ratio is calculated by the following formula (I). Compression ratio (%) = [Thickness before compression (unloaded state) – Thickness after compression] / Thickness before compression × 100 (I) By setting the compression ratio at 5% or more and 65% or less, the bubbles are crushed and the composite particles are brought closer to each other, thereby improving the thermal conductivity. By setting the compression ratio at 7% or more, 10% or more, 15% or more, or even 20% or more, the contact area between the composite particles is increased, and the thermal conductivity can be further increased. In addition, from the viewpoint of bringing the composite particles into contact with each other without destroying the orientation state of the composite particles, it is preferable to set the compression ratio at 60% or less, 55% or less, or even 50% or less.

[0046] The compressed portion may be disposed in a part of the urethane foam molded body, or may be disposed in the entirety. An example of a form in which the entirety is composed of compressed portions is a thermally conductive sheet formed by compressing the entirety of the urethane foam molded body into a sheet shape. When the urethane foam molded body of the present disclosure is used as a thermally conductive material, the compressed portion may be disposed between the heat generating body and the heat dissipating body. In this way, the compressed portion can be made to conform to the deformation of the heat generating body and have high thermal conductivity, and the thermal resistance between the heat generating body and the heat dissipating body can be reduced to enhance heat dissipation. In this case, the compressed portion may be formed in the urethane foam molded body in advance and disposed between the heat generating body and the heat dissipating body, or the urethane foam molded body before compression may be disposed between the heat generating body and the heat dissipating body and used in a compressed state from one side or both sides.

[0047] [Porosity] If the volume of the urethane foam molded body is taken as 100% by volume, the porosity of the parts other than the compressed parts should be 4% by volume or more in order to enable compression to a maximum of 65%. Also, in order to ensure the desired thermal conductivity, the porosity should be 40% by volume or less. When the compressed parts are disposed over the entire urethane foam molded body, "parts other than the compressed parts" refers to the urethane foam molded body before compression.

[0048] The porosity of a urethane foam molded body can be adjusted by the amount of raw material (mixed raw material described below) filled into the foaming mold used to produce the urethane foam molded body. Assuming that the foaming reaction proceeds sufficiently due to the foaming agent, the porosity is calculated by the following formula (II). Porosity (%) = (volume of foam mold - total volume of raw materials to be filled) / volume of foam mold × 100 (II) The porosity of the urethane foam molded body is determined by the unit volume (e.g., 1 cm 3 The volume of the filler and polyurethane foam per unit volume can be calculated using the following formula (III): In formula (III), the volume of the filler and polyurethane foam per unit volume can be calculated, for example, by adding up the filler volume calculated from the mass and specific gravity of the filler contained in the unit volume and the polyurethane foam volume calculated from the mass and specific gravity of the polyurethane foam. Porosity (%) = (unit volume - volume of filler and polyurethane foam in unit volume) / unit volume × 100 (III)

[0049] <Method of manufacturing urethane foam molded body> The method for producing the urethane foam molded article of the present disclosure is not particularly limited. As a preferred embodiment of the method for producing the urethane foam molded article of the present disclosure, the method for producing the urethane foam molded article of the present disclosure includes a composite particle production step, a mixed raw material production step, a foam molding step, and a compression section formation step. Each step will be described below.

[0050] [Composite particle manufacturing process] This process is a process for producing composite particles by stirring a granulation raw material having a powder of thermally conductive particles, a powder of magnetic particles, a powder of insulating inorganic particles mixed as necessary, a binder, and water. The amount of powder and binder used may be appropriately adjusted in consideration of the magnetic field orientation of the composite particles, the electrical insulation and thermal conductivity of the urethane foam molding, etc. For example, the amount of binder mixed is desirably 2% by mass or more when the total mass of the powder to be bonded is 100% by mass, as a necessary and sufficient amount for adhesion of the particles. On the other hand, if the binder is excessive, there is a risk of the composite particles coagulating with each other. For this reason, the amount of binder mixed is desirably 10% by mass or less. It is more preferable to use 5% by mass or less. The binder may be solid or liquid. When a water-soluble powder is used as the binder, it is advisable to add water after stirring the binder and other powder raw materials in advance. By doing so, the aggregation of the particles can be suppressed.

[0051] In the case where the granulation raw material contains a powder of insulating inorganic particles and the insulating inorganic particles are disposed in the outermost layer of the composite particles, this process may include a first stirring process in which a first raw material having a powder of thermally conductive particles, a powder of magnetic particles, a binder, and water is stirred, and a second stirring process in which the powder of insulating inorganic particles is added to the stirred first raw material and further stirred.

[0052] [Mixed raw material manufacturing process] This step is a step of producing a mixed raw material by mixing the powder of the composite particles produced in the previous step, the powder of insulating inorganic particles which is blended as necessary, and a urethane foam resin raw material.

[0053] As described above, the foamed urethane resin raw material may be prepared from raw materials such as polyol, polyisocyanate, catalyst, blowing agent, and foam stabilizer. The mixed raw material can be produced, for example, by mechanically stirring a powder of composite particles, a powder of insulating inorganic particles, and a foamed urethane resin raw material using a stirring blade or the like. In addition, the powder of composite particles and the powder of insulating inorganic particles may be added to at least one of the two components of the foamed urethane resin raw material (polyol raw material, polyisocyanate raw material) to prepare two types of raw materials, and then the two raw materials may be mixed to produce the foamed urethane resin.

[0054] [Foam molding process] In this process, the mixed raw material produced in the previous process is injected into the cavity of a foaming mold, and foam-molded while applying a magnetic field so that the magnetic flux density in the cavity becomes approximately uniform.

[0055] The injection amount of the mixed raw material may be adjusted to obtain the desired porosity, assuming that the foaming reaction is sufficiently promoted by the foaming agent. The magnetic field may be formed in a direction (thermal conduction direction) that orients the composite particles. For example, by arranging magnets near both sides of one end and the other end of the foaming mold so as to sandwich the foaming mold, the magnetic field lines in the cavity can be generated approximately parallel from one end of the cavity to the other end. The magnet may be a permanent magnet or an electromagnet. When an electromagnet is used, the magnetic field formation can be instantly switched on and off, and the strength of the magnetic field can be easily controlled. Therefore, the foaming molding can be easily controlled. In addition, it is desirable that the magnetic field lines that constitute the magnetic field form a closed loop. In this way, leakage of the magnetic field lines is suppressed, and a stable magnetic field can be formed in the cavity.

[0056] In order to form a magnetic field so that the magnetic flux density in the cavity is approximately uniform, the difference in magnetic flux density in the cavity is preferably within ±10%. Within ±5%, and more preferably within ±3%. By forming a uniform magnetic field in the cavity of the foaming mold, the uneven distribution of the composite particles can be suppressed, and the desired orientation state can be obtained. In addition, the foaming molding is preferably performed at a magnetic flux density of 150 mT or more and 350 mT or less. In this way, the composite particles in the mixed raw material can be reliably oriented. It is desirable to apply the magnetic field while the viscosity of the foamed urethane resin raw material is relatively low. If the magnetic field is applied when the foamed urethane resin raw material thickens and the foaming molding is completed to a certain extent, the composite particles are difficult to orient, so it is difficult to obtain the desired thermal conductivity. It is not necessary to apply the magnetic field for the entire time of foaming molding. After the foaming molding is completed in this process, a skin layer may be formed on at least one of one end and the other end of the urethane foam molded body obtained by demolding. The skin layer may or may not be cut off.

[0057] [Compression section formation process] This process is a process in which a part or all of the urethane foam molded body obtained in the previous process is compressed in the direction of heat conduction to form a compressed part. The compressed part may be formed in advance using a device such as a press machine or a compression jig before application to a member, or may be formed by compression with members placed on both sides of the compressed part when applied. In the former case, the pressing time using the device should be 72 hours or more. The compression ratio may be appropriately determined within the range of 5% to 65% so that the desired characteristics are obtained depending on the application.

[0058] <Heat dissipation structure> The heat dissipation structure of the present disclosure is a member that dissipates heat from a heat generating body, and includes a heat dissipation body and the above-mentioned urethane foam molded body of the present disclosure, and a compressed portion of the urethane foam molded body is disposed between the heat generating body and the heat dissipation body. An embodiment of the heat dissipation structure of the present disclosure is shown below. FIG. 1 shows a schematic cross-sectional view of a battery pack in which the heat dissipation structure of the present disclosure is disposed. Regarding the orientation of FIG. 1, the arrangement direction (stacking direction) of the battery cells is the X direction, and of the two directions perpendicular to the X direction, the longitudinal direction of the battery cells is the Y direction, and the short direction (terminal-bottom direction, up-down direction in FIG. 1) is the Z direction. First, the configuration of the battery pack and heat dissipation structure of this embodiment will be described. As shown in FIG. 1, the battery pack 1 has a housing 10, a plurality of battery cells 20, and a heat dissipation structure 30.

[0059] The housing 10 is made of metal and has a box shape. Each of the battery cells 20 is composed of a lithium ion battery and is housed in the housing 10. Each of the battery cells 20 has a rectangular parallelepiped shape and is stacked in the thickness direction (X direction). The heat dissipation structure 30 has a cooling plate 31 and a thermally conductive sheet 32. The cooling plate 31 is made of metal and has a thin plate shape. The cooling plate 31 is disposed on the bottom surface of the housing 10. The thermally conductive sheet 32 ​​is made of the urethane foam molded body of the present disclosure in a form consisting of a compressed portion having a compression rate of 20% as a whole. In the urethane foam molded body, the composite particles are oriented in the Z direction. The thermally conductive sheet 32 ​​is interposed between the stack of battery cells 20 and the cooling plate 31. The thermally conductive sheet 32 ​​has a thickness of 2 mm. The thermally conductive sheet 32 ​​is manufactured by placing an uncompressed urethane foam molded body (thickness: 2.5 mm) on the upper surface of the cooling plate 31 and pressing it from above with a stack of battery cells 20. The battery cells 20 are included in the concept of a heat generating body in this disclosure, and the cooling plate 31 is included in the concept of a heat dissipating body in this disclosure.

[0060] Next, the effects of the heat dissipation structure of this embodiment will be described. The heat conductive sheet 32 ​​constituting the heat dissipation structure 30 is in contact with the bottom surface (XY surface) of the battery cell 20 and the upper surface of the cooling plate 31. The heat conductive sheet 32 ​​has excellent heat conductivity and flexibility capable of following the expansion and contraction of the battery cell 20 during charging and discharging. This improves the heat dissipation from the battery cell 20 to the cooling plate 31. In addition, the heat conductive sheet 32 ​​is relatively lightweight and is unlikely to be pumped out even if the battery cell 20 repeatedly expands and contracts.

[0061] In the above embodiment, the heat generating element is a battery cell, and the heat dissipating element is a cooling plate, but the heat generating element to which the heat dissipating structure of the present disclosure is applied is not limited to this. Examples of the heat generating element include various electronic components such as a CPU and a power supply used in electronic devices. The heat dissipating element is also not particularly limited, and may be a heat sink, a battery pack, or a metal housing of an electronic device. EXAMPLES

[0062] Next, the present disclosure will be described in more detail with reference to examples. In these examples, samples of urethane foam molded bodies having different compression ratios were manufactured, and the relationship between the compression ratio and the thermal conductivity, and the relationship between the compression ratio and the degree of orientation of the composite particles were examined.

[0063] <Sample Production> [Production of composite particles] A granulation raw material containing expanded graphite powder as thermally conductive particles, stainless steel powder as magnetic particles, starch powder as binder, talc powder as insulating inorganic particles, and water was stirred to produce composite particles. First, 1000 parts by mass of expanded graphite powder, 600 parts by mass of stainless steel powder, and 100 parts by mass of starch powder were put into a container of a high-speed stirring type mixer granulator and mixed by blade stirring, and 400 parts by mass of water were added and mixed for 1 minute. Next, 400 parts by mass of talc powder were put in and mixed for another 4 minutes. The stirring speed was 400 rpm. The obtained powder was dried to obtain a powder of composite particles. Details of the materials used are shown in the following (a) to (d). (a) Thermally conductive particles Expanded graphite powder: "EXA-50" manufactured by Fuji Graphite Industries Co., Ltd., median diameter 300 μm. (b) Magnetic particles Stainless steel powder: "AKT" manufactured by Mitsubishi Steel Corporation, median diameter 8.5 to 13.0 μm. (c) Binder Starch powder: "Instant Tender Gel C" manufactured by Nippon Corn Starch Co., Ltd. (d) Insulating inorganic particles Talc powder: "Microace (registered trademark) K-1" manufactured by Nippon Talc Co., Ltd., median diameter 8 μm.

[0064] [Magnetic field molding of urethane foam molding] A urethane foam molded body was manufactured using the powder of the manufactured composite particles and aluminum hydroxide powder as insulating inorganic particles to be dispersed in the base material. First, 100 parts by mass of polyether polyol (manufactured by Sumika Covestro Urethane Co., Ltd., "SBU (registered trademark) Polyol 0248"), 2 parts by mass of diethylene glycol (manufactured by Mitsubishi Chemical Corporation) as a chain extender, 2 parts by mass of water as a foaming agent, 1.5 parts by mass of tetraethylenediamine catalyst (manufactured by Kao Corporation, "Kao Raiser (registered trademark) No. 31"), and 0.5 parts by mass of a silicone foam stabilizer (manufactured by Toray Dow Corning Co., Ltd., "SZ-1333") were mixed to prepare a polyol raw material. In addition, a diphenylmethane diisocyanate (MDI) modified product was prepared as a polyisocyanate raw material. The MDI modified product was produced by mixing polyether polyol (same as above) and 4,4'-diphenylmethane diisocyanate ("Millionate MT" manufactured by Tosoh Corporation) so that the isocyanate (NCO) content was 70% by mass, and reacting for 180 minutes at 100°C under nitrogen purging. Next, 80 parts by mass of composite particle powder and 60 parts by mass of aluminum hydroxide powder ("SB53" manufactured by Nippon Light Metal Co., Ltd., median diameter 55 μm, thermal conductivity 8 W / m·K) were added to 100 parts by mass of the polyol raw material and mixed to prepare a premix polyol. Next, 100 parts by mass of the premix polyol and 10 parts by mass of the polyisocyanate raw material (MDI modified product) were mixed to prepare a mixed raw material.

[0065] The mixed raw material was poured into an aluminum foaming mold (cavity was a rectangular parallelepiped with dimensions of 130 mm length x 130 mm width x 2 mm thickness), and the foaming mold was sealed. The amount of the mixed raw material poured was adjusted so that the void ratio was 40% by volume, assuming that the foaming reaction would proceed sufficiently with water. Then, the foaming mold was placed in a magnetic induction foaming molding device to perform foaming molding. In the cavity of the foaming mold, a uniform magnetic field was formed by magnetic lines of force that were approximately parallel from above to below. The magnetic flux density in the cavity was 200 mT, and the difference in magnetic flux density in the cavity was within ±3%. The foaming molding was performed with a magnetic field applied for the first 2 minutes, and without a magnetic field applied for the following 5 minutes. After the foaming molding was completed, the mold was removed to obtain a urethane foam molded body in which the composite particles were oriented in the thickness direction. The content of the composite particles in the obtained urethane foam molded body was 10% by volume, and the content of the insulating inorganic particles was 10% by volume (in both cases, the volume of the urethane foam molded body was 100% by volume). In the foam molding, the thickness of the foam mold was changed to produce eight types of urethane foam molded bodies with different thicknesses: 2.00 mm, 2.02 mm, 2.04 mm, 2.11 mm, 2.50 mm, 4.00 mm, 5.71 mm, and 6.67 mm.

[0066] [Compression section formation] From each of the eight types of polyurethane foam molded bodies produced, square samples measuring 50 mm long x 50 mm wide were cut out. For the seven types of samples other than the 2.00 mm thick sample, both sides in the thickness direction were clamped with a jig, and the entire sample was compressed to a thickness of 2.00 mm at room temperature and held in this state for 48 hours. In this way, seven types of samples with compression rates of 1%, 2%, 5%, 20%, 50%, 65%, and 70% were produced, and a total of eight types of samples were prepared, including the uncompressed 2.00 mm thick sample.

[0067] <Sample evaluation> The thermal conductivity and the degree of orientation of the composite particles of each of the produced samples were measured by the following method.

[0068] [Thermal Conductivity] The thermal conductivity was measured using "HC-110" manufactured by Eiko Seiki Co., Ltd., which complies with the heat flow meter method of JIS A1412-2:1999.

[0069] [Orientation degree of composite particles] First, the sample was subjected to X-ray CT measurement using a high-resolution 3D X-ray microscope "nano3DX" manufactured by Rigaku Corp. Next, the obtained tomographic image data was subjected to fiber orientation analysis using 3D CT software ("VGStudio (registered trademark) MAX" manufactured by Volume Graphics Inc.) to calculate the degree of orientation of the composite particles.

[0070] [Measurement results] Figure 2 shows the thermal conductivity of the polyurethane foam against the compression ratio. As shown in Figure 2, the thermal conductivity of the sample with a compression ratio of 0% was 0.6 W / m·K, while the thermal conductivity of the sample with a compression ratio of 5% was 1.1 W / m·K. When the compression ratio was 5% or more, the thermal conductivity increased rapidly. In particular, the thermal conductivity of the samples with compression ratios of 20% and 50% was 1.5 W / m·K or more. On the other hand, the thermal conductivity of the sample with a compression ratio of 70% was 0.6 W / m·K, and it was confirmed that the thermal conductivity decreases when the compression ratio is too high. Figure 3 shows the degree of orientation of the composite particles against the compression ratio of the polyurethane foam. As shown in Figure 3, the degree of orientation of the composite particles decreased as the compression ratio increased. From this result, it can be seen that as the compression ratio increases, the inclination of the long axis of the composite particles with respect to the thickness direction increases, and there is a risk of the orientation state being destroyed. For example, the degree of orientation of the composite particles in the sample with a compression ratio of 70% was as small as 0.15, which corresponds to a decrease in thermal conductivity.

[0071] Separately, the presence or absence of pump-out was examined using a sample of the produced urethane foam molded product (thickness 2.00 mm after foam molding). First, the sample was sandwiched between two thin aluminum plates measuring 50 mm long x 50 mm wide x 10 mm thick, and compressed at a compression rate of 30%. Then, it was visually observed whether the sample protruded around the thin plates, and the length of any protruding portion was measured. As a result, the length of the protruding portion of the produced urethane foam molded product sample was less than 5 mm around the entire circumference of the thin plates, and it was determined that there was no pump-out. [Explanation of symbols]

[0072] 1: battery pack, 10: housing, 20: battery cell, 30: heat dissipation structure, 31: cooling plate, 32: thermally conductive sheet.

Claims

1. A base material made of polyurethane foam; a composite particle that is contained in the base material and has thermally conductive particles and magnetic particles bonded to the surfaces of the thermally conductive particles by a binder; The composite particles are oriented in a heat conduction direction, A urethane foam molded article having a compressed portion compressed at a compression rate of 5% to 65% in the heat conduction direction.

2. 2. The urethane foam molded article according to claim 1, wherein a content of the composite particles is 5 volume % or more and 50 volume % or less, where the volume of the urethane foam molded article is 100 volume %.

3. 2. The urethane foam molded article according to claim 1, wherein the porosity of the portion other than the compressed portion is 4 volume % or more and 40 volume % or less, where the volume of the urethane foam molded article is 100 volume %.

4. 2. The urethane foam molded article according to claim 1, wherein the thermally conductive particles are flaky or fibrous, and the degree of orientation of the composite particles in the compressed portion is 0.2 or more.

5. The urethane foam molded article according to claim 1 , wherein the thermally conductive particles comprise expanded graphite particles.

6. The urethane foam molded article according to claim 1 , further comprising insulating inorganic particles dispersed in the base material.

7. The urethane foam molded article according to claim 1 , wherein the compression section is disposed between a heating element and a heat sink.

8. The urethane foam molded article according to claim 1 , wherein the compressed portion comprises the entirety of the urethane foam molded article.

9. A heat dissipation structure that dissipates heat from a heat generating body, A heat sink and the urethane foam molded article according to claim 1, The heat dissipation structure, wherein the compressed portion of the urethane foam molded body is disposed between the heat generating body and the heat dissipating body.

Citation Information

Patent Citations

  • Cooler and structure

    JP2020088108A

  • Thermally conductive sheet, its installation method and manufacturing method

    JP2022121447A

  • Urethane foam molding and method for manufacturing same

    WO2013042611A1